120k views
2 votes
(polynomials) multiply. (x^2-5x)(2x^2+x-3)

A. 2x^4 - 9x^3 - 9x^2 - 15x
B. 2x^4 + 9x^3 - 8x^2 + 15x
C. 4x^4 + 9x^3 - 8x^2 + 15x
D. 2x^4 - 9x^3 - 8x^2 + 15x

2 Answers

5 votes

Answer:

2x^4 - 9x^3 -8x^2 + 15x

Explanation:

(x^2-5x)(2x^2+x-3) distribute first

2x^4

x^2 + x = x^3

5 * 2x^2 x= 10x^3

5x^1+1 = 5x^2

5 * 3x = 15x Put them all together

2x^4 + x^3 - 3x^2 - 10x^3 - 5x^2 + 15x Like terms

2x^4 + x^3 -10x^3 - 3x^2- 5x^2 + 15x Add similar terms

= 2x^4 + x^3 - 10x^3 - 8x^2 + 15x more adding terms

2x^4 - 9x^3 -8x^2 + 15x

Hope my answer has helped you, if not i'm sorry.

User Alina Danila
by
5.1k points
3 votes

For this case we must multiply the following expression:


(x ^ 2-5x) (2x ^ 2 + x-3)

We apply distributive property term to term taking into account that:


+ * - = -\\- * - = +\\x ^ 2 * 2x ^ 2 + x ^ 2 * x-x ^ 2 * 3-5x * 2x ^ 2-5x * x + 5x * 3 =

For powers of the same base, we place the same base and add the exponents:


2x ^ 4 + x ^ 3-3x ^ 2-10x ^ 3-5x ^ 2 + 15x =

We add similar terms:


2x ^ 4-9x ^ 3-8x ^ 2 + 15x

Answer:

OPTION D


2x ^ 4-9x ^ 3-8x ^ 2 + 15x